RESEARCH AND DEVELOPMENT PROJECT SELECTION: A COMPREHENSIVE ANALYSIS OF THE TRENDS AND METHODS - Filiz Turkmen, Gizem; Topcu, Yusuf Ilker (The South African Journal of Industrial Engineering, 2021)
The purpose of this paper is to present a comprehensive literature review of the research and development (R&D) project selection problem since 1977, using the PRISMA method. This study aims (i) to support researchers and practitioners to understand selection methodologies, decision-maker types, and perspectives; (ii) to guide them in choosing the most suitable project selection method; and (iii) to clarify a common confusion by proposing a more precise definition of ‘R&D project selection’ and ‘R&D portfolio selection’. The study also highlights several areas for improvement and the future of project selection techniques for further studies.